Le récit de la translation des reliques de saint Regnobert : histoire d’une éphémère fondation monastique effectuée aux portes de Lisieux sous l’épiscopat de Fréculf - Christophe Maneuvrier (Tabularia)
Although it has been published several times since the 17th century, the tale of the translation of saint Regnobert’s relics remains little known. The identification of place-names and characters makes it possible to propose here a new reading of this text. The latter, written in two stages, first around 856/858 A.D., then around 867/869 A.D., tells of the journey of the relics from Bayeux to the outskirts of the episcopal city of Lisieux. It is indeed at Suiacum, on a land that fell at the time under the juridiction of the bishop of Bayeux, that a little monastic settlement was created around the middle of the 9th century, in order to shelter the saint’s relics. Over the course of its short existence, this monastery received several alms, among which some from Charles the Bald and Queen Ermentrude.